Podcasting as an Intimate Medium - Euritt, Alyn (Routledge Studies in New Media and Cyberculture, 2023)
This book delves into the notion of intimacy as a defining feature of podcasting, examining the concept of intimacy itself and how the public sphere explores the relationships created and maintained through podcasts. The book situates textual analysis of specific American podcasts within podcast criticism, monetization, and production advice. Through analysis of these sources' self-descriptions, the text builds a podcasting-specific framework for intimacy and uses that framework to interpret how podcasting imagines the connections it forms within communities. Instead of intimacy being inherent, the book argues that podcasting constructs intimacy and uses it to define the quality of its own mediation. This book will be of interest to scholars and students of New and Digital Media, Media Studies, Communication Studies, Journalism, Literature, Cultural Studies, and American Studies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a CreativeCommons Attribution-Non Commercial-No Derivatives 4.0 license.